Comunicación asertiva como estrategia para prevenir el bullying en los estudiantes de tercero “A”, de la escuela “18 de Noviembre”, Loja 2016-2017 - Macas Ordoñez, Erika Tatiana (2017)
Bullying or bullying among peers today has become a school problem in children around the world and affects in the psychological, social, academic, and other areas. Therefore the present research called; ASERTIVE COMMUNICATION AS A STRATEGY TO PREVENT BULLYING IN THIRD PARTY "A" STUDENTS, OF THE "NOVEMBER 18" BASIC EDUCATION SCHOOL, LOJA 2016-2017. The research had a preexperimental, descriptive and cross-sectional design; The methods used were: inductive, scientific, synthetic analytical and the statistical of Pearson's linear correlation coefficient; Supported by the use of observation technique and the Cisneros Self-Test instrument of School Harassment. The sample consisted of a total of 30 people, 29 students and one teacher. In the results it was possible to show initially that 48% manifest the existence of Bullying at a high level; 45% state that there is a high level of Bullying; And 7% say that there is an almost high level of Bullying. After the educational alternative applied, the following results were evidenced: 62% showed an almost low level of Bullying; 10% indicated a very low level; 10% show an average level; And 10% showed that there is still a high level of bullying, while 8% showed that there is still a high level of bullying. In conclusion the proposed educational alternative had great effectiveness and therefore it is recommended that it be applied in other educational institutions